“A Juvenile Case” — The History of a Story by Andrey Platonov - Natalya I. Duzhina (Studia Litterarum)
The essay discusses Andrey Platonov’s story “A Juvenile Sea” and its place in his biography. The article describes external circumstances behind the story’s composition, Platonov’s unsuccessful attempts to publish the work as a whole, and how he then went on to rework it into a number of shorter stories. Everything concerning the story is very Platonovian. There is no certainty when it was written; its title is in question since Platonov kept changing it; its images, content, and authorial standpoint are bewildering. The story’s publication history — i.e. the manuscript, reviews of Platonov’s contemporaries and other documentary evidence — cast light on some of these difficulties. Collected together, they constitute an article “A Juvenile Case” — as the story was mistakenly transcribed by the OGPU (security police). The article relies on archival materials. It includes the story’s prehistory, a description of the manuscript and of the passages deleted from this manuscript. The latter help establish the nature of Platonov’s work and authorial standpoint. The article also includes all known references (both formal and casual) to the story by Platonov’s contemporaries and details of Platonov’s attempts to publish a short extract from the story under the title “Construction Materials and Equipment.” The aim of the article is documentary, i.e. to establish a chapter of Platonov’s biography as a writer in the literary context of his time, to collect all factual evidence about the story, and to provide objective information about its real-life context. The article establishes that the story “A Juvenile Sea” was written in the spring of 1932, that its subject matter is intimately connected to local historical events, and that Platonov had not succeeded in writing a work that was socialist in spirit.